Multiparameter microfluidics assay of thrombus formation reveals increased sensitivity to contraction and antiplatelet agents at physiological temperature. Issue 203 (July 2021) - Herfs, Linda; Swieringa, Frauke; Jooss, Natalie; Kozlowski, Mike; Heubel-Moenen, Floor C.J.; van Oerle, René; Machiels, Patric; Henskens, Yvonne; Heemskerk, Johan W.M.
Abstract: Introduction: Current developments to assess qualitative and quantitative platelet traits in flowed whole-blood are based on microfluidic devices that mostly operate at room temperature. However, operation at physiological temperature (37 °C) may increase the assay's sensitivity, and facilitates the comparison to other platelet function tests of the diagnostic laboratory. Materials and methods: We adapted the conventional microspot-based microfluidic device with a simple thermo-coupled pre-heating module. Automated analysis of microscopic images assisted in obtaining five time-dependent parameters of thrombus formation over collagen microspots (shear rate 1000 s −1 ). These modifications allowed rapid testing of control and patient blood samples at physiological temperature. Results and conclusion: The higher temperature enhanced platelet adhesion and aggregation as well as late thrombus characteristics such as size and contraction, when compared to room temperature. Moreover, assessment at 37 °C indicated a time-dependent impairment of the thrombus parameters in blood from patients taking common antiplatelet medication, i . e . aspirin and/or clopidogrel. This pointed to increased contribution of the autocrine platelet agonists thromboxane A2 and ADP in the buildup of contracted thrombi under flow. Overall, this study underlined the advantage of multiparameter assessment of microfluidic thrombus formation in detecting an acquired platelet dysfunction, when operating at physiological temperature. This work may bring microfluidics tests closer to the diagnostic laboratory. Highlights: A microfluidic device was adapted with a thermo-coupled pre-heating module. A multiparameter whole-blood flow test was developed operating at 37 °C. In patient blood thrombus formation was more sensitive to antiplatelet medication.